Room temperature continuous-wave excited biexciton emission in perovskite nanoplatelets via plasmonic nonlinear fano resonance - Chen, Jie (2020)
Biexcitons are a manifestation of many-body excitonic interactions, which are crucial for quantum information and computation in the construction of coherent combinations of quantum states. However, due to their small binding energy and low transition efficiency, most biexcitons in conventional semiconductors exist either at cryogenic temperatures or under femto-second pulse laser excitation. Herein, we demonstrated strong biexciton emissions from CsPbBr3 nanoplatelets with continuous-wave excitation at room temperature by coupling them with a plasmonic nanogap. The exciton occupancy required to generate biexciton was reduced ~106 times in the Ag nanowire–Ag film nanogaps. The extremely large enhancement of biexciton emissions was driven by nonlinear Fano resonance between biexcitons and surface plasmon cavity modes. These results provide new pathways to develop high efficiency non-blinking single photon sources of biexciton (with spectral filter for biexciton), entangled light sources, and lasers based on biexciton states.